How to determine the handedness of single molecules using Coulomb explosion imaging. (29th June 2017) - Pitzer, Martin
Abstract: This tutorial is based on a doctoral thesis that was shortlisted for the 2016 AMOP dissertation prize of the German Physical Society (DPG). The principal achievement of the thesis was to use Coulomb explosion imaging (CEI) to determine the microscopic handedness ('chirality') of molecular structures on a single-molecule level. It thus shows how a technique developed in atomic physics can address a long-standing problem in chemistry. Owing to these disparate backgrounds, the tutorial has two facets: on the one hand, the history of molecular chirality and recent developments are very briefly reviewed. On the other hand, an account is given of different experimental approaches to CEI, on the physical processes in light-induced Coulomb explosion and—most importantly—on the aspects that are relevant when designing and performing such an experiment. As structural chirality occurs only in polyatomic molecules, special attention will be given to multiple ionization and multi-coincidence measurements. A short discussion of the results presented in earlier papers is given, followed by an outlook on experiments that are under way or can realistically be performed within the next years.